PELATIHAN INOVASI OLAHAN COKLAT MENJADI SELAI DAN MASKER COKLAT UNTUK MASYARAKAT DESA TARAHAN - Nabila, Novrilia Atika; Tantri Liris Nareswari; Auli, Winni Nur; Rahayyu, Annisa Maulidia; Rooswita, Putri Amelia; Hidayaturahmah, Rizky (JURNAL ABDIMAS DOSMA (JAD), 2024)
South Lampung Regency is the second largest cocoa bean producer in Lampung Province. This natural resource is very abundant, one of which is in Tarahan Village, South Lampung, but until now it has not been optimally processed and is only sold in the form of dry brown beans which have low selling value. This is because the villagers does not know how to process cocoa beans into cocoa products. Therefore, this service program aims to assist the target community in processing cocoa beans into ready-to-sell products (jam and mask) to improve people welfare. This activity consisted of providing material and training in making jam and chocolate masks for 1 day. After the training, the villagers were able to understand and practice making the chocolate jam and mask. This program is expected to increase chocholate selling value as local regional commodities.